2022
DOI: 10.3390/genes13060977
|View full text |Cite
|
Sign up to set email alerts
|

Watercore Pear Fruit Respiration Changed and Accumulated γ-Aminobutyric Acid (GABA) in Response to Inner Hypoxia Stress

Abstract: Watercore is a physiological disorder which often occurs on the pear fruit and the excessive accumulation of sorbitol in fruit intercellular space is considered to be an important cause of watercore. Our previous studies found that the metabolic disorder of sugars may lead to hypoxia stress and disturb respiration, resulting in aggravated fruit rot and the formation of bitter substances. However, the further changes of respiration and the fruit response mechanism are not well understood. A comprehensive transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In our previous research, the expression of three PpGADs was significantly increased, which correlated with the GABA content in watercore fruit [2]. To further evaluate the transcript abundance of PpGADs, we used PpGAD1 in healthy fruit as a control (CK) and compared the PpGADs expression level again.…”
Section: Expression Pattern Of Ppgads In Watercore Fruitmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous research, the expression of three PpGADs was significantly increased, which correlated with the GABA content in watercore fruit [2]. To further evaluate the transcript abundance of PpGADs, we used PpGAD1 in healthy fruit as a control (CK) and compared the PpGADs expression level again.…”
Section: Expression Pattern Of Ppgads In Watercore Fruitmentioning
confidence: 99%
“…The symptoms of watercore are translucent fruit flesh and watery tissue. Our previous study suggested that watery tissue increased anaerobic respiration and caused the fruit to suffer from hypoxia stress [2]. Under hypoxia stress, plants experience a derangement of the cellular energy metabolism, causing a decrease in the pH in the cytoplasm, the inhibition of the ion transport pathway or nutrient acquisition, and the accumulation of toxic products from anaerobic respiration and reactive oxygen species (ROS) [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hypoxic environment will cause the up-regulated expression of gad , a key gene of the GABA synthesis pathway in plants, which promote the accumulation of GABA ( 37 ). Under anoxic stress conditions, Pyrus pyrifolia showed watercore symptoms where the metabolites succinic acid and GABA were significantly accumulated, accompanied with the up-regulated expression of PpGAD gene which indicates the enrichment of GABA ( 38 ). Nitrogen deficiency has adverse effects on tree growth.…”
Section: Effects Of Gaba On Physiological Activities In Plantsmentioning
confidence: 99%